Indonesian School Management Overseas (Case Study in Indonesia Kuala Lumpur School) - Matin, Matin; Sugiarto, Sugiarto; Pujiastuti, Leni (Universitas Malikussaleh, 2020)
The purpose of this study is to describe and analyze the implementation of the management of the Kuala Lumpur Indonesian School in detail and thoroughly from the research subjects on the background of the study with existing characteristics. The case in this study is the application of management in the field of education which includes curriculum management, student management (students), personnel/member management, management of educational facilities and infrastructure, financial management, management of school relations with the community, and management of special services. This research uses a phenomenological qualitative approach with a case study design at the Kuala Lumpur Indonesia School located at No. 1, Lorong Tun Ismail, Kuala Lumpur, Malaysia, which consists of elementary, junior high, and high school. Data collection techniques are through observation, interviews, and documentation. Data collection techniques with triangulation, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. Based on the analysis of the data it was found that the supporting factors were that the Kuala Lumpur Indonesian School was already running and giving a good role in the implementation of the cultural diplomacy function in Malaysia and the School Financial Management was running well. When teachers whose contracts have expired and must return to Indonesia while substitute teachers have not yet arrived. In student management there is a problem of residence visas, teaching teachers not in accordance with the educational background result in professional competence.